Moléculas fotônicas aplicadas como filtro ótico em laser semicondutor para obtenção de fonte de luz monocromática sintonizável - Pires, Marcus Vinicius do Amaral (Universidade Federal de São Carlos, 2022)
This work demonstrates the application of Photonic Molecules - PMs in spectral engineering and its ability to integrate a complex and compact optical filter, capable of efficiently and tunably filtering broad emission spectra and with many resonances, generated by a semiconductor laser formed by InGaAs/InGaAsP quantum wells. The proposed device was designed using commercial simulation software and using results obtained from the fabrication and characterization of an electronically pumped laser. the signal generated by this laser was coupled to the designed PM that allowed to filter the modes of the multimode laser, proving its ability to select a single resonance, approaching the output of the photonic system of a tunable single-mode laser.
Photonic molecules applied as optical filter in semiconductor laser to obtain tunable monochromatic light source
Keywords: Moléculas Fotônicas; Filtros ópticos; Microcavidades; Laser de microdisco; Laser semicondutor; Photonic Molecules; Optical filters; Microcavities; Semiconductor laser; Microdisk laser; ENGENHARIAS::ENGENHARIA ELETRICA::TELECOMUNICACOES; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS::MATERIAIS E COMPONENTES SEMICONDUTORES